Analisis Problem Based Learning pada Pembelajaran IPS Kelas IV SD Negeri 195 Palembang - Rina Aidiana; Misdalina Misdalina; Ida Suryani (Journal on Education, 2023)
This study aims to determine the factors that influence the successful implementation of the PBL model in social studies learning for students in grade IV A at SD Negeri 195 Palembang. The method used in this study was a qualitative descriptive method. The total number of students examined in this study was 28 students. The techniques for collecting data in this study were observation, interviews, and documentation in the form of the results of students' social studies learning problem-solving skills in solving problems in the form of class IV Natural Resources material at SD Negeri 195 Palembang. The aspects assessed in this study include indicators of social studies problem solving based on the learning material provided by natural resources, namely understanding the problem, making plans, implementing plans and looking back at the answers. From the results of data analysis and discussion, it can be concluded that the teacher succeeded in implementing the PBL model by looking at the factors that influence the success of learning, namely; by preparing learning materials, giving problems at the beginning of learning, preparing learning media and using surrounding media, students understand the material presented by the teacher, there is question and answer communication between teacher and students, using the literacy method of reading, there are rewards (praise to students, scores, stars, prizes), providing reference books to find answers and solutions in solving problems, there are group studies and student discussions, students are enthusiastic and enthusiastic in the learning process, and students are able to present the results of their answers in front of the class.